Factors Related to Fire Fighter Performance - Rosita Ginting; Irmayani; Jul Asdar Putra Aamura; Putri Ashari Visar (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Fire is a type of disaster that frequently occurs in various countries and has the potential to cause significant losses, both in the form of material damage and loss of life. In such conditions, firefighters play a very important role, especially in fire extinguishing efforts and victim evacuation. The performance of firefighters is influenced by various factors, both internal and external to the organization. This study aims to identify and analyze factors related to the performance of firefighters at the Lubuk Pakam Fire Department, Deli Serdang Regency. The study used a quantitative method with a cross-sectional design. The study population included all firefighters serving at the Deli Serdang Fire Department, totaling 30 people. The sampling technique used the total sampling method. Data collection was carried out using a questionnaire covering the variables of facilities and infrastructure, training, counseling, and officer performance. The data obtained were then analyzed using the Chi-Square test with a 95% confidence level. The results showed that 53.3% of respondents had good performance. The results of the study showed a significant relationship between infrastructure (p=0.008) and training (p=0.021) with firefighter performance. Conversely, the community outreach variable did not show a significant relationship with officer performance (p=0.586). Based on these findings, it can be concluded that internal organizational factors, particularly the availability of work facilities and training, play a significant role in improving firefighter performance. Therefore, relevant agencies are advised to continue improving the quality of facilities and infrastructure and to conduct regular training to strengthen officer competency in dealing with fire emergency situations